2020
DOI: 10.5539/jas.v12n12p49
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Employment and Its Impact on the Agricultural Sector Workforce in Trinidad, West Indies

Abstract: The agricultural sector in Trinidad and Tobago is characterized by a labor shortage. A qualitative research design was used to investigate the impact of a national welfare employment program, on the agriculture labor sector. The study recruited n = 19 Community-Based Environmental Protection and Enhancement Program (CEPEP) employees, n = 10 farmers and n = 7 agricultural professionals for in-depth interviews and focus group sessions. A review was conducted of newspaper articles and national budget statements f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Trinidad and Tobago's food import bill doubled from 2004 to 2008, and this trend of increasing food imports becomes more substantial with each passing year [ 35 ]. Researchers reported that Trinidad and Tobago's total food import bill between 2003 and 2016 was approximately USD$8.91 billion or TT$56.9 billion [ 36 ]. In 2013, the economic cost diverted toward food imports was about USD 364 million (about TT$2.5 billion) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trinidad and Tobago's food import bill doubled from 2004 to 2008, and this trend of increasing food imports becomes more substantial with each passing year [ 35 ]. Researchers reported that Trinidad and Tobago's total food import bill between 2003 and 2016 was approximately USD$8.91 billion or TT$56.9 billion [ 36 ]. In 2013, the economic cost diverted toward food imports was about USD 364 million (about TT$2.5 billion) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Food insecurity is one of the known causes of undernutrition and stunting in children, but it has also been linked to obesity [ 39 ]. Food security involves “physical and economic access to sufficient, safe and nutritious food that meets [the] dietary needs and food preferences for an active and healthy life” [ 36 ]. Food security entails having access to sufficient nutritious food.…”
Section: Resultsmentioning
confidence: 99%